2014
DOI: 10.1186/1476-511x-13-79
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of ApoAI gene and sepsis-associated acute lung injury

Abstract: BackgroundApolipoprotein A1 (ApoA1) is the major apoprotein constituent of high density lipoprotein (HDL) which exerts innate protective effects in systemic inflammation. However, its role in the acute lung injury (ALI) has not been well studied. In the present study we investigated the association between polymorphisms of ApoA1 gene and ALI in a Chinese population.MethodsThree polymorphisms of the ApoA1 gene (rs11216153, rs2070665, and rs632153) were genotyped by TaqMan method in 290 patients with sepsis-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In accord with this, we found that the beneficial effect in septic shock of PCSK9 loss-of-function variants was abolished in patients with mutations of the LDLR gene near the site of usual PCSK9 binding to the LDLR (50). In addition, wild-type mice benefitted from (75) and genetic variants of ApoA1 are associated with sepsis-induced acute lung injury in one study (76).…”
Section: Central Role Of Pcsk9 In Pathogen Lipid Clearancementioning
confidence: 98%
“…In accord with this, we found that the beneficial effect in septic shock of PCSK9 loss-of-function variants was abolished in patients with mutations of the LDLR gene near the site of usual PCSK9 binding to the LDLR (50). In addition, wild-type mice benefitted from (75) and genetic variants of ApoA1 are associated with sepsis-induced acute lung injury in one study (76).…”
Section: Central Role Of Pcsk9 In Pathogen Lipid Clearancementioning
confidence: 98%
“…Carriage of the APOA1 -75 AA genotype in the APOA1 promoter, which has reduced promoter activity as compared to the major G allele, has been associated with a higher risk of ALI following cardiopulmonary bypass surgery ( Smith et al, 1992 ; Tu et al, 2013 ). The rs11216153 SNP in the APOA1 gene has also been associated with ALI risk in subjects with sepsis, with the GG genotype and G allele being more common among ALI patients than controls ( Hao and He, 2014 ). However, since this SNP is located in a non-coding region of the APOA1 gene, it is unclear if the association is with the APOA1 gene itself or variants from nearby genes.…”
Section: Acute Lung Injury (Ali) and Acute Respiratory Distress Syndrmentioning
confidence: 99%
“…For rs2070665, the T allele frequency in the Kazakh control group was 32.5%. The allele mutation rate was higher than the foreign report (Henkhaus et al, 2011), but lower than the 42.0% of Chinese nationals reported by Hao and He (2014). The findings indicate that ethnic differences exist in the genotype and allele frequencies of this locus of the APOA1 gene.…”
Section: Discussionmentioning
confidence: 40%